Catalytic cracking aid compositions, processes for their preparation and use

CN118304924BActive Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310018909.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2026-10-16
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

[0006]本发明的目的是为了克服现有技术存在催化裂化反应液化气中烯烃浓度较低的问题,提供一种催化裂化助剂及其制备方法与应用,该催化裂化助剂应用于催化裂化过程中,能够显著提高液化气中烯烃的浓度

Benefits of technology

[0010] The catalytic cracking additive provided by this invention introduces a macroporous silica-boehmite composition during the preparation process, thereby preparing a catalytic cracking additive rich in mesoporous and macroporous structures. Compared with conventional additives, it has abundant 10-60nm mesoporous and macroporous structures. When used in the catalytic cracking process, it can significantly improve the ability of feedstock oil molecules to diffuse into the active centers of molecular sieves, while promoting the rapid diffusion of product olefins into the pores of molecular sieves, avoiding secondary side reactions such as hydrogen transfer of olefin molecules, and significantly increasing the olefin concentration in liquefied petroleum gas. It is especially suitable for processing heavy or inferior feedstock oils with high metal (Ni, V, Fe, etc.) content and has strong resistance to heavy metal pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118304924B_ABST
    Figure CN118304924B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of oil refining catalysts, and discloses a catalytic cracking aid composition, a preparation method and application thereof. The aid composition contains the following components based on the dry basis weight of the aid composition: 30-60 wt% of ZSM-5 zeolite molecular sieve, 5-30 wt% of macroporous silica-pseudo boehmite composition in terms of oxides, 2-40 wt% of clay and 5-50 wt% of aluminum phosphate sol; silica particles are uniformly distributed between pseudo boehmite particles, the macroporous silica-pseudo boehmite composition is a mixed phase structure of pseudo boehmite and amorphous silica, the pore volume of the macroporous silica-pseudo boehmite composition is 0.8-1.4 mg / L, the specific surface area is 220-300 m 2 / g, and the average pore diameter is 16-35 nm. The catalytic cracking aid is applied to a catalytic cracking process, and can significantly improve the concentration of olefins in liquefied gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of refining catalysts, specifically to a catalytic cracking aid composition, its preparation method, and its application. Background Technology

[0002] Catalytic cracking is a crucial process in petroleum refining, converting larger heavy oil molecules in feedstocks into smaller ones to produce light petroleum products such as liquefied petroleum gas (LPG), gasoline, and diesel, as well as chemical products. The most commonly used active component in catalytic cracking catalysts is microporous zeolite material. However, the small pore size of zeolite materials restricts diffusion, hindering the catalytic reaction of large molecules. To achieve efficient conversion of heavy oil molecules, mesoporous acidic catalytic materials are gaining increasing attention. Since the first report of the synthesis of ordered mesoporous silica-alumina materials in 1992, their ordered pore structure and large pore size have facilitated the diffusion of reactant and product molecules. However, due to the weak acidity, poor stability, and the need for template agents in their preparation, large-scale application in catalytic cracking catalysts has not been observed. To overcome the shortcomings of ordered mesoporous silica-alumina materials, researching and developing low-cost and stable non-ordered mesoporous acidic silica-alumina materials for application in catalytic cracking catalysts would offer greater practicality.

[0003] US Patent Application US5045519A discloses a process for preparing an aluminosilicate-based catalyst support. This process involves preparing a high-purity, thermally stable silica-alumina catalyst support containing 0.5-50% silica. The catalyst is obtained by mixing an aluminum-containing compound with silicic acid in an aqueous medium, followed by drying and calcination. The aluminum-containing compound used is composed of C2-C... 20 + Aluminum silicate is obtained by hydrolyzing alkoxyaluminum with water purified by ion exchange, and simultaneously or subsequently adding orthosilicic acid purified by ion exchange to the aluminum-containing compound. Because organic materials such as alkoxyaluminum and orthosilicic acid are used as raw materials, the resulting product has a Na₂O content of less than 50 ppm. This mesoporous aluminum silicate support has a certain degree of acidity, but this process uses organic alkoxyaluminum as the aluminum source and ion-exchanged orthosilicic acid as the silicon source, and strictly controls the Na₂O content to be less than 50 ppm, resulting in high preparation costs.

[0004] Chinese patent application CN106582597A discloses a silicon-modified alumina, its preparation method, and its application. The alumina is modified using silica sol. The process includes: (1) acidifying and solubilizing a pseudoboehmite slurry with an inorganic acid to obtain a pseudoboehmite sol; (2) adding silica sol to the pseudoboehmite sol to obtain a first mixture; (3) adjusting the pH of the first mixture within the range of pH=1-11 according to different requirements for improving the surface Brønsted acid content and pore volume of alumina, and then reacting the silica-modified alumina rich in Brønsted acid (when the pH of the first mixture is adjusted to pH=1-2) or the silica-modified alumina with large pore volume (when the pH of the first mixture is adjusted to pH=10-11) under heating conditions for a period of time to obtain a second mixture; (4) crystallizing the second mixture at 100-120℃ for 12-24h to obtain a third mixture; (5) filtering, washing, drying, and calcining the third mixture to obtain silica-modified alumina. By adjusting the pH of the first mixture, a flexible switch can be achieved between focusing on improving pore volume and focusing on improving Brønsted acid content. The B / L ratio of the silicon-modified alumina rich in Brønsted acid is 0.40-0.95, and the pore volume of the macroporous silicon-modified alumina is 0.8-1.2 cm³. 3 / g. This invention cannot meet the requirements for preparing mesoporous silicon-aluminum materials with pore diameters of 16-30 nm.

[0005] Chinese patent application CN107303484A discloses a method for preparing a silica-containing macroporous alumina support and a hydrotreating catalyst. The support preparation includes: (1) impregnating boehmite dry gel powder with an aqueous solution containing polyols and / or sugars, and then subjecting the impregnated material to hydrothermal carbonization; (2) impregnating carbon black powder with a silica-containing solution, and then mixing the impregnated carbon black powder with the boehmite, extrusion aid, and adhesive solvent from step (1) to form a plastic body, extruding, drying, and then calcining the dried material first under a nitrogen atmosphere and then under an air atmosphere to obtain a silica-containing alumina support. The hydrotreating catalyst contains the above-mentioned support and hydrotreating active components. The alumina support prepared by this method has a large pore volume and pore size while also having high mechanical strength. This support is suitable for the preparation of heavy and residual oil hydrotreating demetallization catalysts and other fields. Summary of the Invention

[0006] The purpose of this invention is to overcome the problem of low olefin concentration in liquefied petroleum gas (LPG) during catalytic cracking reactions in existing technologies, and to provide a catalytic cracking aid, its preparation method, and its application. When applied to the catalytic cracking process, this catalytic cracking aid can significantly increase the olefin concentration in LPG.

[0007] To achieve the above objectives, the first aspect of the present invention provides a catalytic cracking additive composition, wherein, based on the dry weight of the additive composition, the additive composition comprises the following components: 30-60 wt% ZSM-5 zeolite molecular sieve, 5-30 wt% macroporous silica-boehmite composition (based on oxides), 2-40 wt% clay, and 5-50 wt% aluminum phosphate sol; wherein, in the macroporous silica-boehmite composition, the content of silica is 20-60 wt%, the content of alumina is 40-80 wt%, and the content of Na2O is 0.005-0.015 wt%; the silica particles are uniformly distributed among the boehmite particles, the macroporous silica-boehmite composition has a mixed phase structure of boehmite and amorphous silica, the pore volume of the macroporous silica-boehmite composition is 0.8-1.4 mg / L, and the specific surface area is 220-300 m². 2 / g, with pore diameters ranging from 16 to 35 nm.

[0008] A second aspect of the present invention provides a method for preparing a catalytic cracking additive composition, wherein the method comprises the following steps: (1) The macroporous silica-boehmite composition is mixed with clay to obtain a first slurry; (2) The ZSM-5 zeolite molecular sieve is mixed with the first slurry to obtain the second slurry; (3) The aluminum phosphate sol is mixed with the second slurry to obtain the third slurry, which is then spray-dried and calcined to obtain the catalytic cracking aid composition; The total amount of macroporous silica-boehmite composition, ZSM-5 zeolite molecular sieve, clay, and aluminum phosphate sol is 100 parts by weight, the amount of ZSM-5 zeolite molecular sieve is 30-60 parts by weight, the amount of macroporous silica-boehmite composition (calculated as oxide) is 5-30 parts by weight, the amount of clay is 2-40 parts by weight, and the amount of aluminum phosphate sol is 5-50 parts by weight. In the macroporous silica-boehmite composition, the silica content is 20-60% by weight, the alumina content is 40-80% by weight, and the Na₂O content is 0.005-0.015% by weight. Silica particles are uniformly distributed among the boehmite particles. The macroporous silica-boehmite composition has a mixed phase structure of boehmite and amorphous silica. The pore volume of the macroporous silica-boehmite composition is 0.8-1.4 mg / L, and the specific surface area is 220-300 m². 2 / g, with pore diameters ranging from 16 to 35 nm.

[0009] The third aspect of this invention provides the application of the catalytic cracking aid described in the first aspect in the production of low-carbon olefins from heavy or inferior feedstock oil.

[0010] The catalytic cracking additive provided by this invention introduces a macroporous silica-boehmite composition during the preparation process, thereby preparing a catalytic cracking additive rich in mesoporous and macroporous structures. Compared with conventional additives, it has abundant 10-60nm mesoporous and macroporous structures. When used in the catalytic cracking process, it can significantly improve the ability of feedstock oil molecules to diffuse into the active centers of molecular sieves, while promoting the rapid diffusion of product olefins into the pores of molecular sieves, avoiding secondary side reactions such as hydrogen transfer of olefin molecules, and significantly increasing the olefin concentration in liquefied petroleum gas. It is especially suitable for processing heavy or inferior feedstock oils with high metal (Ni, V, Fe, etc.) content and has strong resistance to heavy metal pollution. Attached Figure Description

[0011] Figure 1 This is a pore size distribution diagram of the additive composition of Example 1 of the present invention. Detailed Implementation

[0012] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0013] The first aspect of this invention provides a catalytic cracking additive composition, wherein, based on the dry weight of the additive composition, the additive composition comprises the following components: 30-60 wt% ZSM-5 zeolite molecular sieve, 5-30 wt% macroporous silica-boehmite composition (based on oxides), 2-40 wt% clay, and 5-50 wt% aluminum phosphate sol; wherein, in the macroporous silica-boehmite composition, the content of silica is 20-60 wt%, the content of alumina is 40-80 wt%, and the content of Na2O is 0.005-0.015 wt%; the silica particles are uniformly distributed among the boehmite particles, the macroporous silica-boehmite composition has a mixed phase structure of boehmite and amorphous silica, the pore volume of the macroporous silica-boehmite composition is 0.8-1.4 mg / L, and the specific surface area is 220-300 m². 2 / g, with pore diameters ranging from 16 to 35 nm.

[0014] The catalytic cracking additive of the present invention has good strength and high activity, and causes little reduction in the activity of the main catalyst. It can effectively improve product distribution, reduce dry gas and coke yield, and increase olefin concentration in liquefied gas.

[0015] In this invention, the pore volume, specific surface area, and pore diameter of the macroporous silica-boehmite composition refer to the composition obtained by calcining at 600°C for 3 hours.

[0016] In this invention, the uniform distribution of silica particles among the pseudoboehmite particles was measured by XRD.

[0017] In this invention, the chemical composition of the macroporous silica-boehmite composition was determined by XRF.

[0018] In this invention, the Na2O content in the macroporous silica-boehmite composition is determined by IPC.

[0019] In this invention, the pore volume, specific surface area, and pore diameter of the macroporous silica-boehmite composition are measured by N2 adsorption method.

[0020] In a preferred embodiment, the additive composition comprises, on a dry basis, the following components: 35-50% by weight of ZSM-5 zeolite molecular sieve, 5-25% by weight of macroporous silica-boehmite composition, 5-30% by weight of clay, and 15-40% by weight of aluminum phosphate sol.

[0021] In a preferred embodiment, the total pore volume of the additive composition is not less than 0.18 mg / L, preferably 0.20-0.30 mL / g.

[0022] In a preferred embodiment, the proportion of the medium-sized macropore volume (10-60 nm) in the total pore volume of the additive composition is not less than 60%, preferably 60-80%.

[0023] In a preferred embodiment, the specific surface area of ​​the additive composition is 160-280 m². 2 / g, preferably 170-280m 2 / g.

[0024] In this invention, the total pore volume and specific surface area of ​​the additive composition are determined by low-nitrogen adsorption method, and the proportion of medium- and macropore volume in the 10-60 nm range is determined by peak fitting method.

[0025] In a preferred embodiment, the wear index of the additive composition is not greater than 3% / h, preferably 1-2.8% / h.

[0026] In this invention, the wear index of the catalyst composition was measured by the method NB / SH / T 0964-2017.

[0027] In a preferred embodiment, the ZSM-5 zeolite molecular sieve is selected from at least one of HZSM-5 zeolite molecular sieve, phosphorus- and / or iron-containing ZSM-5 zeolite molecular sieve, and phosphorus- and / or rare earth element-containing ZSM-5 molecular sieve.

[0028] In a preferred embodiment, the molar ratio of silica to alumina in the ZSM-5 zeolite molecular sieve is 20-100.

[0029] In a preferred embodiment, the clay is selected from at least one of kaolin, bentonite, montmorillonite, sepiolite, and diatomaceous earth.

[0030] A second aspect of the present invention provides a method for preparing a catalytic cracking additive composition, wherein the method comprises the following steps: (1) The macroporous silica-boehmite composition is mixed with clay to obtain a first slurry; (2) The ZSM-5 zeolite molecular sieve is mixed with the first slurry to obtain the second slurry; (3) The aluminum phosphate sol is mixed with the second slurry to obtain the third slurry, which is then spray-dried and calcined to obtain the catalytic cracking aid composition; The total amount of macroporous silica-boehmite composition, ZSM-5 zeolite molecular sieve, clay, and aluminum phosphate sol is 100 parts by weight, the amount of ZSM-5 zeolite molecular sieve is 30-60 parts by weight, the amount of macroporous silica-boehmite composition (calculated as oxide) is 5-30 parts by weight, the amount of clay is 2-40 parts by weight, and the amount of aluminum phosphate sol is 5-50 parts by weight. In step (1), the macroporous silica-boehmite composition contains 20-60% by weight of silica, 40-80% by weight of alumina, and 0.005-0.015% by weight of Na₂O. The silica particles are uniformly distributed among the boehmite particles. The macroporous silica-boehmite composition is a mixture of boehmite and amorphous silica. The pore volume of the macroporous silica-boehmite composition is 0.8-1.4 mg / L, and the specific surface area is 220-300 m². 2 / g, with pore diameters ranging from 16 to 35 nm.

[0031] The method provided by the present invention uses a macroporous silica-boehmite composition as one of the raw materials. The macroporous silica-boehmite composition has a large pore diameter. The introduction of the macroporous silica-boehmite composition results in the preparation of a catalytic cracking aid with a rich mesoporous and macroporous structure.

[0032] In a preferred embodiment, the total amount of the macroporous silica-boehmite composition, molecular sieve, clay, and binder is 100 parts by weight, the amount of ZSM-5 zeolite molecular sieve is 35-50 parts by weight, the amount of the macroporous silica-boehmite composition (calculated as oxide) is 5-25 parts by weight, the amount of clay is 5-30 parts by weight, and the amount of aluminum phosphate sol is 15-40 parts by weight.

[0033] In a preferred embodiment, in step (1), the macroporous silica-boehmite composition is prepared by the following method: S1. Select boehmite with a grain size of 3-6nm, a colloidal index >95%, and a Na2O content <0.01% by weight. Acidify the boehmite in the presence of acid to obtain acidified boehmite. Then mix the acidified boehmite with alkaline silica sol to obtain a neutralized slurry. S2. The pH of the neutralized slurry is adjusted to 8-14, preferably 8.5-13, using an alkaline solution. The slurry is then subjected to high-pressure aging, followed by optional separation, drying, and calcination to obtain the macroporous silica-boehmite composition.

[0034] The method for preparing the silica-boehmite composition provided by this invention involves neutralizing an acidified boehmite solution with an ammonium-type alkaline silica sol solution to form a homogeneous mixture of boehmite and silica. After pH adjustment, the neutralized silica-alumina material is subjected to high-pressure aging to further promote the growth of boehmite grains, promote the growth of boehmite and the interaction between silica sol and boehmite, increase the interaction between Si-O-Al, and increase the pore diameter. As a result, the final silica-boehmite composition has the characteristics of a mixture of boehmite and amorphous silica phases with a large pore diameter.

[0035] In a preferred embodiment, in step S1, the acid is selected from inorganic acids and / or organic acids.

[0036] In this invention, the type of acid is not particularly limited and can be any inorganic acid and / or organic acid conventionally defined in the art. Preferably, in step S1, the inorganic acid is selected from at least one of hydrochloric acid, nitric acid, and sulfuric acid, and the organic acid is selected from at least one of formic acid, acetic acid, and oxalic acid.

[0037] In a preferred embodiment, the acidification treatment conditions in step S1 include: a temperature of 20-90°C and a time of 0.5-5h; preferably, the acidification treatment conditions in step S1 include: a temperature of 20-60°C and a time of 0.5-3h.

[0038] In a preferred embodiment, the concentration of the acidified boehmite, calculated as alumina, is 50-150 g / L.

[0039] In a preferred embodiment, in step S1, the conditions for the neutralization reaction include: temperature 23-70°C, pH 1-5, and time 5-60 min. Preferably, in step S1, the conditions for the neutralization reaction include: temperature 30-55°C, pH 1.5-4, and time 10-45 min.

[0040] In the method provided by this invention, the neutralization reaction is carried out at a pH of 1-5, ensuring that the acidified boehmite and silica sol solution simultaneously precipitate under these conditions, forming a homogeneous mixture of silica sol and boehmite, resulting in a silica-boehmite composition with a homogeneous mixed phase. In this invention, by adjusting the flow rates of the silica sol solution and the acidified boehmite, the final silica-boehmite composition is prepared with a silica content of 20-60% by weight, an alumina content of 40-80% by weight, and a Na₂O content of 0.005-0.015% by weight.

[0041] In a preferred embodiment, in step S1, the concentration of silicon oxide in the alkaline silica sol is 10-40% by mass.

[0042] In this invention, there is no particular limitation on the type of alkaline solution, as long as it can achieve a neutralization reaction. Preferably, in step S2, the alkaline solution is an alkaline solution that does not contain metal ions, and is preferably an organic base and / or an inorganic base.

[0043] In a preferred embodiment, the conditions for high-pressure aging in step S2 include: a temperature of 121-220°C, preferably 130-200°C, a pressure of 0.5-3 MPa, preferably 1-2.5 MPa, and an aging time of 1-48 h, preferably 1.5-24 h.

[0044] In a preferred embodiment, step S2 further includes filtering, washing, and drying the aging product to obtain a macroporous silica-boehmite composition. In this invention, the filtration method is not particularly limited and can be any filtration method conventionally defined in the art. In a preferred embodiment, deionized water is used for washing at a temperature of 50-95°C. Specific filtration and washing processes include commonly used vacuum filtration, belt filter filtration, plate and frame filter filtration, and plate and frame filter filtration followed by filter cake re-pulping and plate and frame filter filtration. The specific operation method is not limited in this invention.

[0045] In a preferred embodiment, the drying conditions in step S2 include a temperature of 80-120°C. In this invention, the drying process can be selected from processes such as oven drying, flash drying, and spray drying.

[0046] In a preferred embodiment, the calcination conditions in step S2 include: a temperature of 400-600°C and a time of 0.5-5 hours.

[0047] In this invention, it is understood that the content of each substance in the pore size silica-pseudoboehmite composition has been described above and will not be repeated here.

[0048] In a preferred embodiment, in step (1), the clay is selected from at least one of kaolin, bentonite, montmorillonite, sepiolite and diatomite.

[0049] In a preferred embodiment, in step (1), the first mixing includes mixing the macroporous silica-boehmite composition with clay and water.

[0050] In a preferred embodiment, the conditions for the first mixing include: a mixing time of not less than 15 minutes, preferably 20-120 minutes.

[0051] In a preferred embodiment, in step (1), the solid content of the first slurry is 15-40% by weight.

[0052] In this invention, the specific types of ZSM-5 zeolite molecular sieves mentioned in step (2) have been described in the first aspect and will not be repeated here.

[0053] In a preferred embodiment, in step (2), the conditions for the second mixing include: the mixing time is not less than 15 min, preferably 20-120 min.

[0054] In a preferred embodiment, in step (2), the solid content of the second slurry is 15-40% by weight.

[0055] In a preferred embodiment, in step (3), the conditions for the third mixing include: a mixing time of 10-60 min, preferably 15-45 min.

[0056] In a preferred embodiment, in step (3), the solid content of the third slurry is 15-40% by weight.

[0057] In a preferred embodiment, the roasting conditions in step (3) include: a temperature of 350-550°C and a time of 0.5-5h; preferably, the roasting conditions in step (3) include: a temperature of 400-550°C and a time of 0.5-3h.

[0058] In this invention, the method further includes washing and drying processes after calcination, which can be carried out according to existing methods, and there are no special requirements for this invention.

[0059] The third aspect of this invention provides the application of the catalytic cracking aid described in the first aspect in the production of low-carbon olefins from heavy or inferior feedstock oil.

[0060] In this invention, preferably, the catalytic cracking aid can be used alone in the catalytic cracking reaction, or it can be mixed with a catalytic cracking catalyst conventionally defined in the art for use in the catalytic cracking reaction. When used in combination with a catalytic cracking catalyst, the amount of the catalytic cracking aid is preferably 1-30 wt%, more preferably 1-15 wt%, based on the total amount of the catalytic cracking aid and the catalytic cracking catalyst.

[0061] In this invention, preferably, the characteristic factor K of the heavy or inferior raw oil is less than 12.1.

[0062] In this invention, preferably, the reaction conditions include: a reaction temperature of 500-530℃ and an agent-to-oil weight ratio of 3-7:1.

[0063] The present invention will be described in detail below through embodiments. Unless otherwise specified, all the materials described in the following embodiments are commercially available.

[0064] In the following examples, the raw materials used in preparing the additives are described as follows: kaolin with a solid content of 76 wt%; aluminum oxide content in the aluminum phosphate sol of 22.0 wt%; and HZSM-5 zeolite with a SiO2 to Al2O3 molar ratio of 42, a Na2O content of 3.5 wt%, and a solid content of 75 wt%. Phosphorus-modified ZSM-5 zeolite with a SiO2 to Al2O3 molar ratio of 45, a Na2O content of 0.12 wt%, a P2O5 content of 2.1 wt%, and a solid content of 83 wt%.

[0065] The phase composition of the macroporous silica-boehmite composition described in this invention was characterized by X-ray diffraction (XRD) using a Philips XPERT series D5005 X-ray powder diffractometer. The test conditions were: Cu K α X-ray (λ = 0.154 nm), Ni filter, voltage 40 kV, tube current 30 mA, step size 0.02°, 2 i The scanning range is 5-70º.

[0066] Pore ​​volume was determined using an ASAP 2420 nitrogen adsorption analyzer from Micromeritics, USA. Before measurement, the samples were pretreated under vacuum at 300℃ for 10 h. Pore volume was determined using the single-point adsorption method, and the specific surface area of ​​the samples was calculated using the BET equation.

[0067] In this invention, the relative crystallinity is measured by the Q / SH 361 744 method, that is, by using the external standard method, the relative crystallinity of the sample is calculated by measuring the integrated area of ​​the diffraction peak at 2θ=38.3° of the sample and the standard. The standard used is S87-16b, which was prepared by the Petroleum and Chemical Research Institute. After calibration, the crystallinity of the standard is 98.0%.

[0068] In this invention, the grain size is determined by measuring the integral width β1 of the diffraction peak at 2θ=38.3° using an X-ray diffractometer. The grain size L is calculated according to β1=K×λ / (L×cosθ), where K=1.075, and λ is the wavelength of the Ka1 spectral line of the anodic radiation, which is taken as λ=1.5406×10⁻⁶. -10 rice.

[0069] XRF characterization was performed using a Rigaku Electric Industries, Ltd. (RIGE) 3271 X-ray fluorescence spectrometer. Elemental spectral line intensities were detected using a scintillation counter and a proportional counter, and elemental content was quantitatively analyzed using the external standard method. Powder samples were compressed into tablets, with a rhodium target, laser voltage of 50 kV, and laser current of 50 mA.

[0070] To determine the Na content in raw materials and products using ICP, weigh 0.50 g of the sample (accurate to 0.0001 g), place it in a PTFE beaker, add 5 mL of hydrochloric acid, heat at low temperature until the sample is completely dissolved, transfer to a 100 mL volumetric flask, dilute to the mark, shake well, and determine the sodium content using inductively coupled plasma atomic emission spectrometry (ICP-AES). Perform a blank test along with the sample.

[0071] Example 1 Take 190g of pseudoboehmite (solubility index 97.0%, grain size 4.3nm, pore volume 0.43mL / g, specific surface area 231m²). 2 Acidified boehmite solution was prepared by mixing 500 mL of 0.19N dilute nitric acid (containing 0.005% Na2O) with 810 mL of deionized water at a temperature of 60℃ for 2 hours. 333 g of industrial ammonium silica sol JN-30 (Qingdao Chengyu Chemical Co., Ltd., containing 30% silica and 0.012% Na2O) was added to deionized water to prepare 1000 mL of silica sol solution.

[0072] The acidified boehmite solution and silica sol solution were added concurrently to a neutralization reactor with an effective volume of 3.0 L under controlled flow conditions. The neutralization reaction was carried out at a controlled temperature of 40 °C, a pH of 2.8, and a residence time of 30 min.

[0073] 40 mL of concentrated ammonia was added to the slurry after neutralization to adjust the pH to 9.0. The slurry was then transferred to a high-pressure reactor, which was sealed and heated to 180 °C for 12 h. After naturally cooling to room temperature, the slurry was spray-dried to obtain a silica-boehmite composition PS1. PS1 was calcined at 600 °C for 3 h to obtain a silica-alumina composition AS1. XRD characterization showed that PS1 had a mixture of amorphous silica and boehmite phases, as shown in Figure 2. i The relative crystallinity and grain size of the pseudoboehmite calculated at 38° are shown in Table 1. AS1 has a mixture of amorphous silica and γ-alumina phases. The chemical composition of AS1 was characterized by XRF, and the results are listed in Table 1.

[0074] Add 7g of kaolin and 7g of a silica-pseudoboehmite composition PS1 to 36g of water and stir for 90 minutes to obtain a first slurry. Add HZSM-5 zeolite slurry (containing 60g of HZSM-5 molecular sieve with a solid content of 35% by weight) to the first slurry and continue stirring for 30 minutes to obtain a second slurry. Add 181g of aluminum phosphate sol to the second slurry and continue stirring for 45 minutes. Spray dry the resulting total slurry to form a shape, and then calcine at 550℃ for 2 hours to obtain the catalytic cracking aid ZC1 described in this invention. The pore size distribution diagram of the catalytic cracking aid ZC1 is shown below. Figure 1 As shown, the obtained additive has a rich mesoporous and macroporous structure in the 10-60 nm range.

[0075] Example 2 The silica-boehmite composition PS1 was prepared according to the method of Example 1.

[0076] Add 20g of kaolin and 21g of a silica-pseudoboehmite composition PS1 to 108g of water and stir for 60 minutes to obtain a first slurry; add HZSM-5 zeolite slurry (containing 47g of HZSM-5 molecular sieve and a molecular sieve slurry solid content of 38% by weight) to the first slurry and continue stirring for 30 minutes to obtain a second slurry; add 136g of aluminum phosphate sol to the second slurry and continue stirring for 30 minutes; spray dry the resulting total slurry to form a shape, and then calcine at 500℃ for 2 hours to obtain the catalytic cracking catalyst additive ZC2 described in this invention.

[0077] Example 3 The silica-boehmite composition PS1 was prepared according to the method of Example 1.

[0078] Add 13g of kaolin and 36g of a silica-pseudoboehmite composition PS1 to 126g of water and stir for 60 minutes to obtain a first slurry; add HZSM-5 zeolite slurry (containing 36g of HZSM-5 molecular sieve and a molecular sieve slurry solid content of 35% by weight) to the first slurry and continue stirring for 30 minutes to obtain a second slurry; add 160g of aluminum phosphate sol to the second slurry and continue stirring for 30 minutes; spray dry the resulting total slurry to form a shape, and then calcine at 550℃ for 1.5 hours to obtain the catalytic cracking catalyst ZC3 described in this invention.

[0079] Comparative Example 1 Following the method of Example 1, except that the slurry after neutralization reaction of acidified boehmite solution and silica sol solution was not adjusted with concentrated ammonia, and the slurry was directly transferred to a high-pressure reactor. The reactor was sealed, heated to 150°C and held at that temperature for 5 hours. After naturally cooling to room temperature, the slurry was spray-dried to obtain a silica-boehmite composition CPS1. CPS1 was calcined at 600°C for 3 hours to obtain a silica-alumina composition CAS1. XRD characterization showed that CAS1 had a mixture of amorphous silica and boehmite phases, according to the boehmite phase diagram 2. i The relative crystallinity and grain size of the pseudoboehmite calculated at 38° were characterized by XRF method, and the pore volume, specific surface area and pore diameter were measured by N2 adsorption method, as shown in Table 1.

[0080] The auxiliary agent was prepared according to the method of Example 1 to obtain the comparative auxiliary agent DC1.

[0081] Comparative Example 2 Following the method of Example 1, except that after neutralizing the slurry with acidified boehmite solution and silica sol solution, 53 mL of concentrated ammonia was added to adjust the pH to 11.5. The slurry was heated to 90°C and held at that temperature for 5 hours in an aging reactor. After naturally cooling to room temperature, the slurry was spray-dried to obtain a silica-boehmite composition CPS2. CPS2 was then calcined at 600°C for 3 hours to obtain a silica-alumina composition CAS2. XRD characterization showed that CPS2 had a mixture of amorphous silica and boehmite phases, as shown in Figure 2. i The relative crystallinity and grain size of the pseudoboehmite were calculated at 38°. CAS2 has a mixture of amorphous silica and γ-alumina. The chemical composition of CAS2 was characterized by XRF method. The pore volume, specific surface area and pore diameter of CAS2 were measured by N2 adsorption method, as shown in Table 1.

[0082] The auxiliary agent was prepared according to the method of Example 1 to obtain the comparative auxiliary agent DC2.

[0083] Comparative Example 3 Following the method of Example 1, except that the slurry after neutralization reaction of the acidified boehmite solution and silica sol solution was not adjusted for pH or heated, but directly left to stand for 5 hours. The slurry was then spray-dried to obtain a silica-boehmite composition CPS3. CPS3 was calcined at 600°C for 3 hours to obtain a silica-alumina composition CAS3. XRD characterization showed that CPS3 had a mixture of amorphous silica and boehmite phases, as shown in Figure 2. i The relative crystallinity and grain size of the pseudoboehmite were calculated at 38°. CAS3 has a mixture of amorphous silica and γ-alumina. The chemical composition of CAS3 was characterized by XRF method. The pore volume, specific surface area and pore diameter of CAS3 were measured by N2 adsorption method, as shown in Table 1.

[0084] The auxiliary agent was prepared according to the method of Example 1 to obtain the comparative auxiliary agent DC3.

[0085] Example 4 Take 380g of high-purity pseudoboehmite powder (colloidal solubility index 97.5%, grain size 6.1nm, pore volume 0.55mL / g, specific surface area 220m²). 2 Acidified pseudoboehmite solution was prepared by adding 1000 mL of 0.19N dilute nitric acid and 1620 mL of deionized water to 1 g of industrial ammonium silica sol JN-30 (Qingdao Chengyu Chemical Co., Ltd., 30% silica by weight, 0.012% Na2O by weight) to deionized water to prepare 6000 mL of silica sol solution.

[0086] The solution was added concurrently to a 10L neutralization reactor at a controlled flow rate. The neutralization temperature was controlled at 43℃, pH at 3.1, and residence time at 30min for the neutralization reaction. 180mL of concentrated ammonia was added to the slurry after neutralization to bring the pH to 11.5. The slurry was then transferred to a high-pressure reactor, sealed, and heated to 180℃ for 2 hours at a pressure of 2.5MPa. After naturally cooling to room temperature, the slurry was spray-dried to obtain a silica-boehmite composition PS1. PS1 was calcined at 600℃ for 3 hours to obtain a silica-alumina composition AS1. XRD characterization showed that PS1 had a mixture of amorphous silica and boehmite phases, as shown in Figure 2. iThe relative crystallinity and grain size of the pseudoboehmite calculated at 38° are shown in Table 1. AS1 has a mixture of amorphous silica and γ-alumina phases. The chemical composition of AS1 was characterized by XRF, and the results are listed in Table 1.

[0087] Add 26g of kaolin and 14g of a silica-pseudoboehmite composition PS2 to 110g of water and stir for 60 minutes to obtain a first slurry; add HZSM-5 zeolite slurry (containing 41g of HZSM-5 molecular sieve and a molecular sieve slurry solid content of 35% by weight) to the first slurry and continue stirring for 30 minutes to obtain a second slurry; add 160g of aluminum phosphate sol to the second slurry and continue stirring for 30 minutes; spray dry the resulting total slurry to form a shape, and then calcine at 500℃ for 2 hours to obtain the catalytic cracking aid ZC4 described in this invention.

[0088] Example 5 The silica-boehmite composition PS2 was prepared according to the method in Example 4.

[0089] Add 6 g of kaolin and 28 g of a silica-pseudoboehmite composition PS2 to 90 g of water and stir for 60 minutes to obtain a first slurry; add HZSM-5 zeolite slurry (containing 41 g of HZSM-5 molecular sieve, with a molecular sieve slurry solid content of 35% by weight) to the first slurry and continue stirring for 30 minutes to obtain a second slurry; add 181 g of aluminum phosphate sol to the second slurry and continue stirring for 30 minutes, spray dry the resulting total slurry to form a shape, and then calcine at 500°C for 2 hours to obtain the catalytic cracking catalyst ZC5 described in this invention.

[0090] Comparative Example 4 The commercially available Siral40 from Sasol was used as CPS4. XRD characterization revealed that CPS4 possessed a mixture of amorphous silica and pseudoboehmite phases, as shown in Figure 2. i The relative crystallinity and grain size of the pseudoboehmite were calculated at 38°. CAS4 has a mixture of amorphous silica and γ-alumina. The chemical composition of CAS4 was characterized by XRF method. The pore volume, specific surface area and pore diameter of CAS4 were measured by N2 adsorption method, as shown in Table 1.

[0091] Catalytic cracking aids were prepared according to the method in Example 5 to obtain comparative catalyst DC4.

[0092] Table 1

[0093] As shown in Table 1, compared with the comparative example, the silica-boehmite composition prepared in this invention has a higher pore volume and a higher pore size, both greater than 16 nm.

[0094] Table 2

[0095] As can be seen from the data in Table 2, the additive containing the silica-boehmite composition according to the present invention has a high pore volume, with the 10-60 nm pore volume accounting for more than 60% of the total pore volume.

[0096] The following examples illustrate the catalytic cracking performance of the catalytic cracking aid provided by the present invention and its ability to increase the olefin concentration in liquefied gas.

[0097] The additives ZC1-ZC5 prepared in Examples 1-5 of this invention were pre-impregnated in kerosene solutions of nickel naphthenate and vanadium naphthenate, respectively, to achieve nickel and vanadium concentrations of 1500 ppm and 3000 ppm, respectively. They were then aged at 800°C with 100% steam for 4 hours in a fixed-bed aging apparatus. The aged additives were then mixed with HSC industrial balancing agent (provided by Sinopec Catalyst Qilu Branch, main properties shown in Table 3) in different proportions to form catalyst mixtures. Evaluation was then conducted on an ACE unit. The feedstock used for evaluation was a low-quality feedstock with high heavy metal content; the properties of the feedstock are shown in Table 4. The reaction temperature, catalyst-to-oil ratio, weight hourly space velocity, and evaluation results are listed in Table 5.

[0098] Wherein, conversion rate (%) = gasoline yield (%) + liquefied petroleum gas yield (%) + dry gas yield (%) + coke yield (%) LPG olefin concentration (%) = (propylene + butene) yield / LPG yield × 100% Catalytic cracking of the same feedstock oil was carried out according to the methods of Examples 1-5, except that the additives provided in this invention in the catalyst mixture were replaced with the additives prepared in Comparative Examples 1-4. The evaluation results are listed in Table 5.

[0099] Table 3

[0100] Table 4

[0101] Table 5

[0102] Continued from Table 5

[0103] As can be seen, compared with Comparative Examples 1-3, the heavy oil yield of Example 2 of the present invention is lower, while the total yield of liquefied petroleum gas (LPG) and gasoline is higher, and the olefin concentration in the LPG is increased. This indicates that the ZSM-5 zeolite-containing additive prepared by the present invention using a macroporous silica-boehmite composition has excellent resistance to heavy metal contamination and excellent olefin selectivity.

[0104] Compared to Comparative Example 4, Example 5 of the present invention showed a lower heavy oil yield, while the total yields of gasoline and LPG were comparable, and the olefin concentration in LPG increased by 3 percentage points. This indicates that the ZSM-5 zeolite additive prepared using a macroporous silica-boehmite composition has higher heavy oil cracking capacity and excellent resistance to heavy metal contamination, as well as excellent LPG olefin selectivity.

[0105] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A catalytic cracking additive composition, characterized in that, Based on the dry weight of the additive composition, the additive composition comprises the following components: 30-60 wt% ZSM-5 zeolite molecular sieve, 5-30 wt% macroporous silica-boehmite composition (based on oxides), 2-40 wt% clay, and 5-50 wt% aluminum phosphate sol; wherein, in the macroporous silica-boehmite composition, the content of silica is 20-60 wt%, the content of alumina is 40-80 wt%, and the content of Na2O is 0.005-0.015 wt%; the silica particles are uniformly distributed among the boehmite particles, the macroporous silica-boehmite composition has a mixed phase structure of boehmite and amorphous silica, the pore volume of the macroporous silica-boehmite composition is 0.8-1.4 mL / g, and the specific surface area is 220-300 m². 2 / g, with pore diameters of 16-35nm; The pore volume, specific surface area, and dilatant pore diameter of the macroporous silica-boehmite composition refer to the composition obtained by calcining at 600°C for 3 hours.

2. The adjuvant composition according to claim 1, wherein, Based on the dry weight of the additive composition, the additive composition comprises the following components: 35-50% by weight of ZSM-5 zeolite molecular sieve, 5-25% by weight of macroporous silica-boehmite composition (based on oxides), 5-30% by weight of clay, and 15-40% by weight of aluminum phosphate sol.

3. The adjuvant composition according to claim 1, wherein, The total pore volume of the additive composition is not less than 0.18 mL / g.

4. The adjuvant composition according to claim 3, wherein, The total pore volume of the additive composition is 0.2-0.3 mL / g.

5. The adjuvant composition according to claim 1, wherein, In the additive composition, the proportion of the volume of macropores (10-60 nm) in the total pore volume is not less than 60%.

6. The adjuvant composition according to claim 5, wherein, In the additive composition, the volume of macropores (10-60 nm) accounts for 60-80% of the total pore volume.

7. The adjuvant composition according to claim 1, wherein, The specific surface area of ​​the additive composition is 160-280 m². 2 / g.

8. The adjuvant composition according to claim 7, wherein, The specific surface area of ​​the additive composition is 170-280 m². 2 / g.

9. The adjuvant composition according to any one of claims 1-8, wherein, The wear index of the additive composition is no greater than 3% / h.

10. The adjuvant composition according to claim 9, wherein, The wear index of the additive composition is 1-2.8% / h.

11. The adjuvant composition according to any one of claims 1-8, wherein, The ZSM-5 zeolite molecular sieve is selected from at least one of HZSM-5 zeolite molecular sieve, phosphorus- and / or iron-containing ZSM-5 zeolite molecular sieve, and phosphorus- and / or rare earth element-containing ZSM-5 molecular sieve. And / or, the clay is selected from at least one of kaolin, bentonite, montmorillonite, sepiolite and diatomite.

12. A method for preparing a catalytic cracking additive composition, wherein, The method includes the following steps: (1) The macroporous silica-boehmite composition is mixed with clay to obtain a first slurry; (2) The ZSM-5 zeolite molecular sieve is mixed with the first slurry to obtain the second slurry; (3) The aluminum phosphate sol is mixed with the second slurry to obtain the third slurry, which is then spray-dried and calcined to obtain the catalytic cracking aid composition; The amounts of the macroporous silica-boehmite composition, clay, ZSM-5 zeolite molecular sieve, and aluminum phosphate sol used in the prepared catalytic cracking aid composition, based on the dry weight of the catalytic cracking aid composition, are such that the catalytic cracking aid composition contains the following components: 30-60% by weight of ZSM-5 zeolite molecular sieve, 5-30% by weight of macroporous silica-boehmite composition (based on oxides), 2-40% by weight of clay, and 5-50% by weight of aluminum phosphate sol. In the macroporous silica-boehmite composition, the silica content is 20-60% by weight, the alumina content is 40-80% by weight, and the Na₂O content is 0.005-0.015% by weight. Silica particles are uniformly distributed among the boehmite particles. The macroporous silica-boehmite composition has a mixed phase structure of boehmite and amorphous silica. The pore volume of the macroporous silica-boehmite composition is 0.8-1.4 mL / g, and the specific surface area is 220-300 m². 2 / g, with a pore diameter of 16-35nm; wherein, the pore volume, specific surface area and pore diameter of the macroporous silica-boehmite composition refer to the composition obtained by calcining at 600℃ for 3h.

13. The method according to claim 12, wherein, in, The amounts of the macroporous silica-boehmite composition, clay, ZSM-5 zeolite molecular sieve, and aluminum phosphate sol used are such that, based on the dry weight of the catalytic cracking aid composition, the catalytic cracking aid composition contains the following components: 35-50 wt% ZSM-5 zeolite molecular sieve, 5-25 wt% macroporous silica-boehmite composition (based on oxides), 5-30 wt% clay, and 15-40 wt% aluminum phosphate sol.

14. The method according to claim 12 or 13, wherein, In step (1), the macroporous silica-boehmite composition is prepared by the following method: S1. Select boehmite with a grain size of 3-6nm, a colloidal index >95%, and a Na2O content <0.01% by weight. Acidify the boehmite in the presence of acid to obtain acidified boehmite. Then, mix the acidified boehmite with alkaline silica sol for neutralization reaction to obtain neutralized slurry. S2. The pH of the neutralized slurry is adjusted to 8-14 using an alkaline solution, and then subjected to high-pressure aging. After drying, the macroporous silica-boehmite composition is obtained. In step S2, the conditions for high-pressure aging include a temperature of 121-220℃.

15. The method according to claim 14, wherein, In step S2, an alkaline solution is used to adjust the pH of the neutralized slurry to 8.5-13.

16. The method of claim 14, wherein, In step S1, the acid is selected from inorganic acids and / or organic acids; And / or, in step S1, the acidification treatment conditions include: a temperature of 20-90℃ and a time of 0.5-5h; And / or, in step S1, the concentration of the acidified pseudoboehmite, calculated as alumina, is 50-150 g / L.

17. The method according to claim 16, wherein, In step S1, the inorganic acid is selected from at least one of hydrochloric acid, nitric acid and sulfuric acid, and the organic acid is selected from at least one of formic acid, acetic acid and oxalic acid.

18. The method according to claim 16, wherein, In step S1, the acidification treatment conditions include: a temperature of 20-60℃ and a time of 0.5-3h.

19. The method of claim 14, wherein, In step S1, the conditions for the neutralization reaction include: temperature 23-70℃, pH 1-5, and time 5-60 min.

20. The method according to claim 19, wherein, In step S1, the conditions for the neutralization reaction include: a temperature of 30-55°C, a pH of 1.5-4, and a time of 10-45 min.

21. The method according to claim 14, wherein, In step S1, the concentration of silicon oxide in the alkaline silica sol is 10-40% by mass.

22. The method according to claim 14, wherein, In step S2, the alkaline solution is an alkaline solution that does not contain metal ions; And / or, in step S2, the conditions for high-pressure aging include: temperature of 130-200℃, pressure of 0.5-3MPa, and aging time of 1-48h; And / or, step S2 further includes filtering, washing and drying the aging product to obtain a macroporous silica-boehmite composition. And / or, the amount of the pseudoboehmite and alkaline silica sol is such that the content of silica in the obtained macroporous silica-pseudoboehmite composition is 20-60% by weight and the content of alumina is 40-80% by weight.

23. The method according to claim 22, wherein, In step S2, the alkaline solution is an organic base and / or an inorganic base.

24. The method according to claim 22, wherein, In step S2, the conditions for high-pressure aging include: pressure of 1-2.5 MPa and aging time of 1.5-24 h.

25. The method according to claim 22, wherein, In step S2, the drying conditions include a temperature of 80-120°C.

26. The method according to claim 12 or 13, wherein, In step (1), the clay is selected from at least one of kaolin, bentonite, montmorillonite, sepiolite and diatomite.

27. The method according to claim 12 or 13, wherein, In step (1), the first mixing includes mixing the macroporous silica-boehmite composition with clay and water.

28. The method according to claim 12 or 13, wherein, In step (1), the conditions for the first mixing include: the mixing time is not less than 15 minutes.

29. The method according to claim 28, wherein, In step (1), the conditions for the first mixing include a mixing time of 20-120 min.

30. The method according to claim 12 or 13, wherein, In step (1), the solid content of the first slurry is 15-40% by weight.

31. The method according to claim 12 or 13, wherein, In step (2), the ZSM-5 zeolite molecular sieve is selected from at least one of HZSM-5 zeolite molecular sieve, ZSM-5 zeolite molecular sieve containing phosphorus and / or iron, and ZSM-5 molecular sieve containing phosphorus and / or rare earth elements.

32. The method according to claim 12 or 13, wherein, In step (2), the molar ratio of silicon dioxide to aluminum oxide in the ZSM-5 zeolite molecular sieve is 20-100.

33. The method according to claim 12 or 13, wherein, In step (2), the conditions for the second mixing include: the mixing time is not less than 15 minutes.

34. The method according to claim 33, wherein, In step (2), the conditions for the second mixing include a mixing time of 20-120 min.

35. The method according to claim 12 or 13, wherein, In step (2), the solid content of the second slurry is 15-40% by weight.

36. The method according to claim 12 or 13, wherein, In step (3), the conditions for the third mixing include a mixing time of 10-60 min.

37. The method of claim 36, wherein, In step (3), the conditions for the third mixing include a mixing time of 15-45 min.

38. The method according to claim 12 or 13, wherein, In step (3), the solid content of the third slurry is 15-40% by weight.

39. The method according to claim 12 or 13, wherein, In step (3), the calcination conditions include a temperature of 350-550℃ and a time of 0.5-5h.

40. The method according to claim 39, wherein, In step (3), the calcination conditions include: a temperature of 400-550℃ and a time of 0.5-3h.

41. The application of the catalytic cracking additive according to any one of claims 1-11 in the production of low-carbon olefins from heavy or inferior feedstock oil.

Citation Information

Patent Citations

  • Silicon-modified alumina, as well as preparation method and application thereof

    CN106582597A

  • Preparation method of silicon-containing macroporous alumina carrier and hydrotreating catalyst

    CN107303484A

  • Process for the preparation of a catalyst carrier based on aluminosilicates

    US5045519A

  • Cracking catalyst containing mesoporous silica-alumina materials

    CN102078821A

  • Composition of boehmite and silicon-containing compound and silicon oxide-alumina prepared from same

    CN102160996A